Influence of gut microbiome composition on effect variations of anti-cholesterol treatment among individual mice - Hyemin Oh; Yohan Yoon (Food Science and Human Wellness)
This study investigated if the variation in the effect of anti-cholesterol (AC) treatment on individual mice are related to gut microbiome composition. The bile salt hydrolase (BSH) activity of 23 commercial fermented milk products was examined to select a fermented milk product for AC treatment. Mice were fed to different diets for 6 weeks: high- fat (60% of total calories from fat; D1), high-dietary fibre (20% cellulose; D2), and low-fat (17.2% of total calories from fat; D3) diets to change their gut microbiomes. Subsequently, faecal microbiome was transplanted (FMT) into mice treated with high cholesterol diet contained 2% cholesterol, followed by AC or non-AC (sterile tap water, STW) treatments. Control groups with normal (NC) and high-cholesterol diets (PC) were prepared for both AC and STW treatment. All experimental groups were subjected to serum and liver cholesterol, cholesterol metabolism-related (CMR) gene expression, and intestinal microbiome analyses. D3-FMT mice showed the most significant enhancements in cholesterol ratio and decreased hepatic cholesterol levels with AC treatment. Moreover, upregulation of the Cyp7a1 gene expression was observed in this group. Furthermore, the intestinal microbiome analysis indicated higher abundances of BSH-producing Eubacterium, Bifi dobacterium, and Parabacteroides in the D3-FMT + AC group compare to others, potentially contributing to increased bile acid synthesis.